Numerical methods in computational finance a partial differential equation (PDE/FDM) approach - Duffy, Daniel J. (John Wiley & Sons Ltd., 2022)
"Ordinary differential equations and partial differential equations form the basis for modelling many kinds of phenomena in areas such as science, engineering, computational finance and more generally, mathematical physics. There are currently no books on the market which can guide a reader with no prior knowledge of PDEs through the basics and onto advanced applications."--